Time and Image in Julián Ríos' "Sombreros para Alicia": Towards an infantile position. - Fumis, Daniela (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
This paper aims to analyze Sombreros para Alicia (Ríos, 1993) as a complex cultural object in which the image functions as a disruptive element. In this sense, the work is installed as a diverse textual device that questions itself about the time and conditions of figuration in transit on different materialities. Our hypothesis mantains that, in the exploration of the image, the dimension of the infantile is projected as a key operative of the imagination, where the voice crosses the visual materiality and it manages to displace the borders of story towards an open textuality.
Keywords: time; diverse textualities; visuality; infantile position